Changing multi-scale spatiotemporal patterns in food security risk in China. (15th January 2023) - Fei, Li; Shuang, Ma; Xiaolin, Liu
Abstract: Food security was not only an important cornerstone of China's national rejuvenation, but also a matter of achieving the UN's Sustainable Development Goals. The spatial explicit and multi-scale comparative study of China's food security risk pattern was insufficient. Therefore, this study explored the spatio-temporal evolution and scale differences of food security risk pattern in China at micro- (pixel: 1km × 1 km), meso- (county) and macro (provincial) scales by constructing Food Security Risk Assessment models and Food Security Indexes (FSI) that were applicable to various scales, and provided theoretical basis and data support for the country and governments at all levels to formulate food security guarantee strategies. The results showed that the food security risk is quite different on different sides of Ejina-Longhai Line in 2018 at micro-scale. The food security situation in the area east of the Ejina-Longhai Line was generally good, while the area west of the Ejina-Longhai Line had higher food security risks. From 1990 to 2018, China's food security risks were spatially positively correlated and have significant global spatial agglomeration characteristics. In 1990, 2000 and 2018, the local spatial autocorrelation of food security risk at micro- and meso-level was similar. In the last decade of the 20th century, the food security situation in China showed a deteriorating trend due to the difference in the growth rate of total grain output and total population. Since the beginning of the 21st century, rapid increase in grain yields significantly reduced food security risks in China. The changes in food security index at micro- and meso-scales had a high similarity, however, the evaluation results at the meso-scale would underestimate the national food security risks. In addition, the larger the range (scale) of the evaluation unit, the more drastic the temporal variation in food security index, that is, the lower the stability. Scale differences and lower stability lead to evaluation results at the macro-scale that underestimate food security risks in the year of good harvest and overestimate food security risks in the year of poor harvest.